ALHAGI MAURORUM AND TAMARIX APHYLLA -TWO MEDICINAL WEEDS MENTIONED IN HOLY QURAN AND AHADITH AND THEIR ETHNOMEDICINAL USES IN DISTRICT RAJHANPUR OF PAKISTAN - Aslam, Muhammad Shahzad; Ahmad, Muhammad Syarhabil (Universal Journal of Pharmaceutical Research, 2016)
The present research work is based on two medicinal weeds: Alhagi maurorum and Tamarix aphylla (L.) mentioned in the 57 Ayat of Sura Al-Baqarah and 16 Ayat of Sura Saba in Holy Quran respectively. These plants were collected from Rajhanpur District, Punjab, Pakistan. The foremost purpose of this study is to document the knowledge of the ethnomedicinal significance of these plants in the light of Islam. An extensive and complete data was recorded. The comprehensive morphological character of these species was discussed. Botanical names, family, Quranic name, Arabic name, English name, Vernicular name, habit and habitat, distribution, parts used, medicinal uses are documented and references cited from Holy Quran, Ahadith. Peer Review History: Article received on- 7 August; Revised 11 September; Accepted 14 October; Available online 15 November 2016 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Dr. Navin Goyal, Himachal Institute of Pharmacy, HP, India, drgoyal79@gmail.com Dr. Mohamed Said Fathy Al-Refaey , University of Sadat City, Menofia, Egypt, Mohamed.said@fop.usc.edu.eg